Considerações sobre o treinamento ambiental na indústria do petróleo - Freitas, Maximiliano (2005)
This study aims at discussing how environmental education projects are implemented on offshore drilling units and how the workers on board relate to these activities and to environmental issues in general. My experiences in planning, designing, implementing and evaluating these projects in Brazil and abroad made me question whether these environmental education projects are an efficient tool for environmental awareness, leading to an actual reflection on these matters, or if they only contribute to the non-critical reproduction of the sustainability speech. The comments of the employees and their answers to the questionnaires show that they recognize the importance of environmental conservation and their roles in spreading this environmental knowledge . However it is necessary to make sure that such projects are appropriate to the workers reality, and that they are given theoretical and practical tools to criticize and apply this knowledge in their every day life, acting as agents of the behavioural change regarding the environment.